2016
DOI: 10.1148/radiol.2016151301
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Radiologic Assessment of Chemotherapy Response in Ewing Sarcoma Can Be Used to Predict Clinical Outcome

Abstract: Purpose:To compare the agreement of three-dimensional (3D) tumor measurements for therapeutic response assessment of Ewing sarcoma according to the Children's Oncology Group (COG) criteria, one-dimensional (1D) Response Evaluation Criteria in Solid Tumors (RECIST), and two-dimensional (2D) measurements defined by the World Health Organization (WHO) with tumor volume measurements as the standard of reference and to determine which method correlates best with clinical outcomes. Materials andMethods:This retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…Given that 8 cm estimates a tumor larger than 200 mL but is not associated with inferior local tumor control may indicate maximum tumor dimension measurements are an inadequate prognostic variable with contemporary treatment. In fact, Aghighi et al (14) demonstrated that 3-dimensional tumor measurements for ES significantly correlated with clinical outcomes compared with 1- or 2-dimensional measurements, in which the correlation was weaker or not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Given that 8 cm estimates a tumor larger than 200 mL but is not associated with inferior local tumor control may indicate maximum tumor dimension measurements are an inadequate prognostic variable with contemporary treatment. In fact, Aghighi et al (14) demonstrated that 3-dimensional tumor measurements for ES significantly correlated with clinical outcomes compared with 1- or 2-dimensional measurements, in which the correlation was weaker or not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Since HisRes has been identified as a prognostic factor, image‐based response might well correlate with HisRes . Previously published reports on imaging based tumor response cited only limited numbers of patients and focused more on response during late induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of the RECIST update in 2009 (RECIST 1.1), the lack of rigorous clinical validation and of widespread access to these newer imaging approaches prevented their implementation and adoption. However, in recent years, a number of publications have demonstrated the high reproducibility and interobserver reliability of volume measurements using semiautomated tumor segmentation technique implemented in commercially available15, 16, 17, 18 or in‐house software 19. The estimated ellipsoidal volume has been suggested as an approximation for software‐calculated actual volume to overcome limitations related to software availability and has shown good correlation to actual volume 15, 18.…”
mentioning
confidence: 99%
“…However, in recent years, a number of publications have demonstrated the high reproducibility and interobserver reliability of volume measurements using semiautomated tumor segmentation technique implemented in commercially available15, 16, 17, 18 or in‐house software 19. The estimated ellipsoidal volume has been suggested as an approximation for software‐calculated actual volume to overcome limitations related to software availability and has shown good correlation to actual volume 15, 18. Moreover, for a number of cancers 3D assessments enable to capture finer changes in tumor size,17, 18 and better correlates to long‐term clinical outcome, such as OS,2, 18, 21 compared to 1D measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation